Fish Feeder And Monitoring Temperature Control System Menggunakan Metode Protoype pada Akuarium Ikan Hias Koki Berbasis Internet Of Things - AB Susanto; Sindu Arianto; Joko Purnomo; Sulistiyasni . (Jurnal ICT : Information Communication & Technology, 2021)
IoT in this research serves to integrate and connect all electronic devices using the internet network. This system will make it easier for users to feed fish from a distance and get information about the state of water.Arduino utilizes the ATMega microprocessor to control a variety of sensors. For example, to monitor the condition of a room and make it possible to "feel" the conditions in the room even though it is monitored remotely.The method used in this research is Prototype because it is very good for solving misunderstanding problems between users and analysts. Researchers designed and implemented an IoT-based temperature control system for remote feeding and monitoring in aquarium ornamental chefs. This system uses an Android-based smartphone connected to the NodeMcu Microcontroller to send the latest temperature information and provide an early warning if the temperature in the aquarium.